2001
DOI: 10.1152/jappl.2001.91.5.2351
|View full text |Cite
|
Sign up to set email alerts
|

Increases in intramuscular pressure raise arterial blood pressure during dynamic exercise

Abstract: This investigation was designed to determine the role of intramuscular pressure-sensitive mechanoreceptors and chemically sensitive metaboreceptors in affecting the blood pressure response to dynamic exercise in humans. Sixteen subjects performed incremental (20 W/min) cycle exercise to fatigue under four conditions: control, exercise with thigh cuff occlusion of 90 Torr (Cuff occlusion), exercise with lower body positive pressure (LBPP) of 45 Torr, and a combination of thigh cuff occlusion and LBPP (combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 31 publications
4
40
2
Order By: Relevance
“…Mechanical distortion of receptive fields of sensory nerve endings in contracting muscle may evoke the exercise pressor reflex in humans [26]. The mechanoreceptor is tonically active and appears to be primarily responsible for the exercise pressure reflex-induced elevation in arterial blood pressure during dynamic strain in humans [27]. It may initiate the cardiovascular and the ventilatory response during the first phase ("fast response") of the cardiovascular response to exercise [9].…”
Section: Consequences Of Metaboreflex and Mechanoreflex Activationmentioning
confidence: 99%
“…Mechanical distortion of receptive fields of sensory nerve endings in contracting muscle may evoke the exercise pressor reflex in humans [26]. The mechanoreceptor is tonically active and appears to be primarily responsible for the exercise pressure reflex-induced elevation in arterial blood pressure during dynamic strain in humans [27]. It may initiate the cardiovascular and the ventilatory response during the first phase ("fast response") of the cardiovascular response to exercise [9].…”
Section: Consequences Of Metaboreflex and Mechanoreflex Activationmentioning
confidence: 99%
“…Notwithstanding, we observed that G-suit inflation at rest resulted in a 7% increase in MAP, no change in LVEDVr, and a reduction in HR and LVEF. Stickland et al (41) reported that LBPP elicited increases in resting right atrial pressure and pulmonary artery wedge pressure, whereas other investigators have demonstrated that LBPP during leg exercise mediated an increase in MAP, attributed to pressure-sensitive mechanoreceptors (14). The fall in LVEF at rest in the present study could be attributed to a rise in increased MAP secondary to a modest rise in sympathetic outflow known to occur after inflation or activation of muscle mechano-reflexes independent of central cardiovascular control (44).…”
Section: Effects Lbpp On LV Filling At Restmentioning
confidence: 97%
“…In efforts to characterize pulmonary circulatory dynamics, an improved version of the anti-G-suit was used to develop LBPP during dynamic leg exercise in a recent study and reported significantly elevated cardiac filling pressures but not in CO or SV (41). Similarly, Gallagher et al (14), using both cuff inflation and pneumatic-based LBPP, found no improvements in CO during progressive leg ergometry. The difference in findings may be due to body position, since standing may pose a greater orthostatic challenge, enabling a larger effect to be observed (37).…”
Section: Lbpp and LV Function During Arm Exercisementioning
confidence: 99%
“…However, in a series of experiments designed to preferentially accentuate mechanoreceptor activation above the metaboreceptor activation in healthy subjects, we employed leg compression using medical antishock trousers (MAST) with and without epidural anesthesia at rest (115) and with and without leg compression using MAST during steady-state exercise while constructing baroreflex function curves (32), lower body positive pressure (LBPP) at rest and during exercise (111), and 4) LBPP with and without thigh-cuff occlusion at 90 mmHg (30). In a separate investigation, the subjects performed submaximal dynamic exercise with and without epidural anesthesia with construction of the baroreflex function curves (103).…”
Section: Arterial Baroreflexmentioning
confidence: 99%